The Role of Ribosomal Protein S6 Kinases in Plant Homeostasis - Obomighie, Irabonosi; Lapenas, Kestutis; Murphy, Billy E.; Bowles, Alexander M. C.; Bechtold, Ulrike; Prischi, Filippo (Frontiers in Molecular Biosciences, 2021)
The p70 ribosomal S6 kinase (S6K) family is a group of highly conserved kinases in eukaryotes that regulates cell growth, cell proliferation, and stress response via modulating protein synthesis and ribosomal biogenesis. S6Ks are downstream effectors of the Target of Rapamycin (TOR) pathway, which connects nutrient and energy signalling to growth and homeostasis, under normal and stress conditions. The plant S6K family includes two isoforms, S6K1 and S6K2, which, despite their high level of sequence similarity, have distinct functions and regulation mechanisms. Significant advances on the characterisation of human S6Ks have occurred in the past few years, while studies on plant S6Ks are scarce. In this article we review expression and activation of the two S6K isoforms in plant and we discuss their roles in mediating responses to stresses and developmental cues.